2008
DOI: 10.1155/2009/154610
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution and Chemical Profile of Cauvery River Water

Abstract: Analysis of water, plankton, fish and sediment reveals that the Cauvery River water in the downstream is contaminated by certain heavy metals. Water samples have high carbonate hardness. Concentrations of all elements and ions increase in the downstream. Main ions are in the following order: Na > HCO3>Mg > K > Ca> Cl > SO4. Heavy metal concentration in water was Cr >Cu ≈ Mn > Co > Ni > Pb > Zn, in fish muscles Cr > Mn > Cu > Ni > Co > Pb ≈ Zn, in phytoplanktens C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 4 publications
1
61
1
3
Order By: Relevance
“…Of the 16 heavy metals, manganese did not show strong affinity with any of the metals, but, exhibits weak correlation under factor 1 implying the source of this could also be considered wastewater from industries. Surface water pollution of heavy metals due to disposal of industrial wastes in the Cauvery river has been reported earlier (Begum et al 2009;INSA 2011;Krishnamoorthy and Nagarajan 2013). Groundwater in this part of the Cauvery river basin is polluted with silver, lead and nickel in all the sampling locations and parts of the area are polluted with aluminium, boron, cadmium, copper, iron and manganese.…”
Section: Sources Of Heavy Metalsmentioning
confidence: 79%
See 1 more Smart Citation
“…Of the 16 heavy metals, manganese did not show strong affinity with any of the metals, but, exhibits weak correlation under factor 1 implying the source of this could also be considered wastewater from industries. Surface water pollution of heavy metals due to disposal of industrial wastes in the Cauvery river has been reported earlier (Begum et al 2009;INSA 2011;Krishnamoorthy and Nagarajan 2013). Groundwater in this part of the Cauvery river basin is polluted with silver, lead and nickel in all the sampling locations and parts of the area are polluted with aluminium, boron, cadmium, copper, iron and manganese.…”
Section: Sources Of Heavy Metalsmentioning
confidence: 79%
“…Past studies in different parts of the Cauvery river basin which originates in Karnataka state and extends till Tamil Nadu include monitoring of dissolved silica levels in surface waters along the course of the Cauvery river and results indicated no major changes in the dissolved silica and main solutes over last 30 years (Meunier et al 2015). Surface water samples collected along the course of the river in Karnataka showed concentrations of chromium, manganese, nickel and lead above the maximum permissible limits and copper and zinc within the limits of Bureau of Indian Standards (BIS) for drinking water quality (Begum et al 2009). Surface waters of river Cauvery in Tamil Nadu tested in 2010 revealed concentrations of cadmium, chromium, copper, iron, nickel, lead, zinc and mercury within the prescribed limits (Krishnamoorthy and Nagarajan 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chloride increases the electrical conductivity of water and thus increases its corrosivity. In metal pipes, chloride reacts with metal ions to form soluble salts (8), thus increasing levels of metals in drinking-water. In lead pipes, a protective oxide layer is built up, but chloride enhances galvanic corrosion (14).…”
Section: Chloridementioning
confidence: 99%
“…[12] Nickel was analyzed to be present in the concentration of 46.2 mg/kg -76.9 mg/kg in PRM and 45.3 mg/kg -76.2 mg/kg in POM. Nickel is suspected to be an essential trace elements for plants as well as for animals and used principally in its metallic form combined with other metals and nonmetals as alloys [13] Metals such as chromium, copper, and nickel have interacted with organic matter in aqueous phase and settled to the bottom, resulting in a high concentration of these metals in the sediment [14]. The higher amount of nickel concentration is due to lithogenic sources,industrial wastages and sometimes-anthropogenic activities.…”
Section: Fig 1 Figmentioning
confidence: 99%
“…Potential anthropogenic sources of Ti in the environment include paint pigments (TiO 2 pigment accounts for the largest use of the element) and its alloys with Al, Mo, Mn and Fe, which are used extensively in aircraft, ship and missile manufacture. Metals such as chromium, copper, and nickel have interacted with organic matter in aqueous phase and settled to the bottom, resulting in a high concentration of these metals in the sediment [14] Cobalt, Lead and Cadmium has a concentration below detectable level in the sampling locations from the Poondi reservoir to the city belt.They show a maximum concentration of 12.3 mg/kg , 17.9 mg/kg , 0.154 mg/kg respectively in PRM and 11.6 mg/kg , 17.9 mg/kg , 0.135 mg/kg respectively in POM. The lower values of lead might be attributed to less solubility of Pb containing minerals in natural water [24,25].…”
Section: Fig 1 Figmentioning
confidence: 99%